Capacitação profissional para segurança do paciente crítico em terapia renal substitutiva - Pereira Júnior, Tomas (2019)
INTRODUCTION: Patient safety is currently one of the most important issues for health system managers worldwide. It is defined as the set of initiatives or practices designed to avoid, prevent and reduce the adverse outcomes resulting from health care with the reduction of potential risks. Patients with severe clinical conditions, multi-morbimortality, intense and fragmented use of the health system and high level of hospital exposure, are characterized by the increased risk of adverse events, including in this group, those with renal disease in renal replacement therapy. The Patient Safety Culture is defined by the Agency for Healthcare Research and Quality (AHRQ) as the product of values, attitudes, skills and behavioral patterns that determine the commitment, style and proficiency of managing a healthy and safe. In this context, we understand health education as a cornerstone for strengthening a system based on good practices, and indispensable for the improvement of professional skills. We use innovative initiatives called active teaching methodologies, where the student plays a central role in the process and is challenged to "learn to learn". OBJECTIVE: To train health professionals in the area of patient safety in order to reduce the incidence of adverse events during dialysis. METHODOLOGY: it was conducted a research-action study through an extension event of UFRN, directed to Doctors, Nurses and undergraduates from both areas, in the workshop format, through two modules, with a 10-hour workload, using conventional and active teaching methodologies. RESULTS: It was offered 33 vacancies, distributed among the internal and external public, only 22 students started the course, 94% of Nursing (05 graduates and 16 undergraduates) and only 01 undergraduate in Medicine. After the theoretical module, we performed an online evaluation with multiple choice questions, with a mean of 82%. During the practical module it was performed O.S.C.E. with two stations, with an average of 80.3% of hits for the group. It was also conducted an online satisfaction survey with 80% of satisfied participants. CONCLUSION: The authors considered the extension event to be successful in its objectives, observing the need for its continuity and structural improvement, as well as better adjustment in its programming, stimulating the new active teaching methodologies and developing strategies that increase motivation of health professionals in participating in professional training events.